The Possible Role of Epstein Barr Virus and Its Latent Proteins in Systemic Lupus Erythematosus Patients (Iraqi Journal of Medical Sciences, 2020)
Background:Systemic lupus erythematosus is a chronic, systemic, idiopathic autoimmune disease. One of the suggested environmental factors that lead to development of systemic lupus erythematosus is infection with Epstein-Barr virus.Objective: First, detection and quantification of Epstein-Barr virus in peripheral blood of systemic lupus erythematosus patients compared to control. Second, estimation of mRNA level of latent and lytic genes and compare them with control groups.Methods: This a case-control study conducted on systemic lupus erythematosus patients during the period from (December 2018 to March 2019). A total of 40 patients were involved in this study. Blood samples were taken from Baghdad Teaching Hospital of Medical City. On the other hand, 40 blood samples were collected from apparently healthy subjects, as control samples from blood donor center in Al-Imamein Al-kadhimein Medical City.Results: Eleven of forty (27.5%) of systemic lupus erythematosus patients were positive with Epstein-Barr virus at mean viral load 815.72 copy/ml with (P value 0.59). And the rate of Epstein-Barr virus detection in blood of patients group was highest in severe cases rather than in less severe ones. Only 2/40 (5%) of control subjects were positive with Epstein-Barr virus at much lower mean viral load, 64.75 copy/ml (P Value 0.34). The expression of the latent genes in patients versus control groups, was 100% versus 77.5% for EBNA-2, 50% versus 15% for EBNA-3C, 82.5% versus 97.5% for late membrane protein -1, and 85% versus 75% for EA/D, respectively. EBNA-2 expression showed significant direct proportional correlation with viral load.Conclusion: Increased rate of Epstein-Barr virus DNA detection in systemic lupus erythematosus group compared to control group and higher rate of viral DNA detection within severe cases might indicate a possible defect in controlling viral infection and increased number of latent infected cell in systemic lupus erythematosus. Also increased positive EBNA-2 and EBNA-3C expression in systemic lupus erythematosus group rather than in control group indicates that these Epstein-Barr virus proteins might have ability to disrupt the normal immune system, and might trigger and/or promote the autoimmune status.Keywords: EBV, SLE, EBNA-2, EBNA-3C, LMP-1, EA/DCitation: Abdullah ZF, Abdulamir AS, Gorial FI. The possible role of Epstein Barr virus and its latent proteins in systemic lupus erythematosus patients. Iraqi JMS. 2020; 18(1): 4-11. doi: 10.22578/IJMS.18.1.2
Keywords: EBV; SLE; EBNA2; EBNA3C; LMP1; EAD